2010
DOI: 10.1111/j.1600-0722.2010.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Dentin surface treatment using a non‐thermal argon plasma brush for interfacial bonding improvement in composite restoration

Abstract: The objective of this study is to investigate the treatment effects of non-thermal atmospheric gas plasmas on dentin surfaces for composite restoration. Extracted unerupted human third molars were used by removing the crowns and etching the exposed dentin surfaces with 35% phosphoric acid gel. The dentin surfaces were treated by using a non-thermal atmospheric argon plasma brush for various durations. The molecular changes of the dentin surfaces were analyzed using FTIR/ATR and an increase in carbonyl groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
4
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(176 citation statements)
references
References 20 publications
5
155
4
12
Order By: Relevance
“…Regarding the modification process, EDX/XPS studies affirmed significant increase in oxygen content on NTAP-treated dental surfaces, reflecting the important role of reactive oxygen species in introducing polar, oxygen-containing groups to the substrates (Koban et al 2011;Silva et al 2011;Lehmann et al 2013;Valverde et al 2013;Chen et al 2014). XPS narrow scans suggested that NTAP treatment induced substantial increase in C-O-, O=C-O-, and CO 3 2-signals on enamel (Lehmann et al 2013), and FTIR analysis revealed an increase in the amount of carbonyl groups (1,760 cm -1 ) on demineralized dentin collagen (Ritts et al 2010).…”
Section: Dental Surface Modificationmentioning
confidence: 99%
“…Regarding the modification process, EDX/XPS studies affirmed significant increase in oxygen content on NTAP-treated dental surfaces, reflecting the important role of reactive oxygen species in introducing polar, oxygen-containing groups to the substrates (Koban et al 2011;Silva et al 2011;Lehmann et al 2013;Valverde et al 2013;Chen et al 2014). XPS narrow scans suggested that NTAP treatment induced substantial increase in C-O-, O=C-O-, and CO 3 2-signals on enamel (Lehmann et al 2013), and FTIR analysis revealed an increase in the amount of carbonyl groups (1,760 cm -1 ) on demineralized dentin collagen (Ritts et al 2010).…”
Section: Dental Surface Modificationmentioning
confidence: 99%
“…Atmospheric-pressure cold plasma -a complex mixture composed of ions, energetic free radicals, electrons, atoms, and molecules generated by gas discharge-has attracted much interest in biomedicine because of its potential applicability in bacterial inactivation 13,14) , tooth whitening 15,16) , blood coagulation 17) , and cancer therapy 18) . In recent years, researchers reported that plasma could be used as an economical and effective means to modify dental materials' surfaces [19][20][21][22][23] . Previous researches confirmed that after heat-cured acrylic resin was treated with cold plasma, it increased the shear bond strength between heat-cured acrylic resin and self-curing acrylic resin 21) .…”
Section: Introductionmentioning
confidence: 99%
“…Embora seja uma tecnologia, no presente momento, de alto custo para uso em consultório, o plasma vem mostrando resultados promissores em relação a atividade antimicrobiana e adesão 6,[8][9][10][11][12][13] . O presente estudo avaliou o efeito do plasma de oxigênio na superfície dentinária, uma vez que este tratamento poderia levar a um aumento na rugosidade desta superfície e a criação de grupamentos funcionais 13,[16][17][18] , que poderiam neutralizar o efeito deletério do oxigênio nascente gerado pelo hipoclorito de sódio.…”
Section: Discussionunclassified
“…Plasmas não térmicos ou ainda plasmas atmosféricos são gases parcialmente ionizados, que contêm partículas altamente reativas, incluindo átomos eletronicamente excitados, moléculas, íons e espécies de radicais livres, cuja fase gasosa permanece próxima da temperatura ambiente 5,6 . Dependendo da composição química do plasma ou gás, estas espécies altamente reativas podem reagir com a superfície, limpando, causando uma erosão (etching), combinando-se com a mesma e formando uma fina camada de recobrimento por plasma, e, desta forma, alterar as características da superfície 6,7 .…”
unclassified